Analisis Penguasaan Konsep Tentang Struktur Lewis Siswa SMAN 1 Kabila - Moh. Fajri Langgene; Opir Rumape; Masrid Pikoli; Wiwin Rewini Kunusa; Julhim S. Tangio; Mangara Sihaloho (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This research aims to asses high scool students’ Masteri of lewis structures for chemical compounds at SMA Negeri 1 Kabila Employs a descriptive qualitative approach with subjects including Class X-V (18 Students), Class X-VII (19 Students), and Class XII-V (20 students), The research instrument used is a pre-test questionnaire comprising 15 multiple-choice questions on lewis structures. Data were analyzed based on students’ performance in answering question related to chemical bonding. Results indicate the mastery abilyti of class X-V students based on the overall test results obtained at 75.67% class x-VII students at 85.26%, and Class X-VIII students at 76.30% (Very, puor, category) therefore, it is necessary to enhace students’ mastery ability.